Organic matter quality and management effects on enrichment of soil organic matter fractions in contrasting soils in Zimbabwe - Mapfumo, Paul; Mtambanengwe, F.; Vanlauwe, Bernard (Springer, 2007)
Maintenance of soil organic matter (SOM) at levels that sustain optimal supply of soil nutrients and enhance efficiency of externally added fertilizers is a major challenge for smallholder farming systems of southern Africa. A study was conducted to quantify the interactive effects of organic resource quality and management on SOM formation and subsequent maize yields under contrasting soil types. Crotalaria juncea L., Calliandra calothyrsus Meissn., cattle manure, maize (Zea mays L.) stover and Pinus patula Schiede and Schltdl. and Cham. sawdust were applied at 1.2 and 4 t C ha?1 at Domboshawa and Makoholi Experimental Stations, simulating some of the soil amendments commonly available on smallholder farms. Soils at Domboshawa are sandy clay loams with 220 g clay kg?1 while the sandy soils at Makoholi had <100 g clay kg?1. At 12 14 weeks after incorporation, organic resource quality effects on particulate organic matter (POM) C enrichment were most significant (p < 0.01) in the macro-POM (250 2,000 ?m diameter) fraction of both soil types constituting 15 30% of total soil C on coarse sand soil and 5 10% on sandy clay loam soils. The highest increases were under C. calothyrsus, manure and sawdust treatments. There was evidence of sub-soil enrichment under these two treatments on sandy soils at different sites. While no significant treatment effects were observed on the size of organo-mineral fraction, there was a significant (p < 0.05) separation of treatments in terms of potential mineralizable N from the same fraction. On coarse sands, organo-mineral fraction under medium to high-quality materials such as manure and C. juncea released ?50 mg N kg?1, compared to 8 18 mg N kg?1 from sawdust and maize stover, suggesting that such materials enhanced the N-supply capacity of this fraction without necessarily increasing its size. The same trends were observed under sandy clay loams although, in contrast to coarse sands, the high-quality materials released no more than 25 mg N kg?1, suggesting that the added C was protected against short-term mineralization. These contrasting properties were also reflected in maize yield patterns. On sandy clay loams, a significant linear relationship between maize yield and the amount of mineralizable N in the macro-POM fraction (R 2 = 0.50; p < 0.01) was evident, while the best predictor for maize yield on coarse sands was the amount of mineralizable N from the organo-mineral fraction (R 2 = 0.86). We concluded that maize productivity on contrasting soil types hinges on different soil organic fractions and therefore require different management strategies. Sustainability of cropping on sandy soils is likely to depend on a regular supply of high-quality C materials, which enhance the nutrient supply capacity of the small organo-mineral fraction. Under the relatively C protective sandy clay loams, it is apparently the size of the macro-POM fraction which largely determines crop yields in the short-term.